The Ayacucho militias as agents of reconstruction and social transformation in the Peruvian civil war (1980-2000) - Fumerton, Mario A. (2024)
This contribution examines why and how civilian militias, called rondas, self-defense committees (CAD) or anti-subversive civil defense (DECAS), emerged during the civil war in Peru. It seeks to explain how they evolved and interacted with other political and social actors at various levels of society during this war; and how they affected the dynamics of daily life during and after the period of political conflict. Most studies on the subject have emphasized the negative aspect of the militias for the excesses they perpetrated, and little attention has been paid to the decisive role they played in the defeat of the Shining Path, under the supervision of the Armed Forces. This text highlights the role of the militias as agents of social reconstruction and positive transformations in the Andean areas of the country, particularly in Ayacucho.